Polymorphism Identification of Pit1 Gene in Indonesian Buffaloes (Bubalus bubalis) and Holstein-Friesian Cows - R Misrianti; C Sumantri; A Farajallah (Faculty of Animal Science, Bogor Agricultural University, 2010)
Pit-1 gene has been identified as the pituitary specific transcription factor that regulates the expression of the growth hormone (GH) and prolactin (PRL) genes in the anterior pituitary. The use of polymorphic markers in breeding programmes could make selection more accurate and efficient. A total of 320 Indonesian buffaloes from four populations and 45 FH cows from nine populations were genotyped for polymorphism of Pit1|Hinf1 gene by the polymerase chain reaction and restriction fragment length polymorphism (PCR-RFLP) methods. The gene polymorphism was detected only in FH cattle. The frequency of AA, AB, and BB genotype was 2%, 44%, and 53% respectively. The frequency of A allel was 25% and B allel was 75%, but no polymorphism was detected in 320 Indonesia buffaloes.